Urgency Pre-Merger Notification System in Indonesia Perspective Maqashid Sharia: Comparative Indonesia and South Korea - Kusnadi, Egi Hadi; Su'udi, Muhammad Arif (TAWAZUN: Journal of Sharia Economic Law, 2025)
Merger is an economic activity carried out by business actors with the aim of developing their business. Companies that conduct mergers can become dominant business actors (dominant markets) so that they have the potential to abuse their dominant position. This study examines the mechanism and assessment of merger notifications in Indonesia and South Korea. The research method used is normative research using a comparative approach, a legal and regulatory approach, and a Maqashid Sharia approach. The results of the study show that South Korea uses the Pre-Merger Notification System, while Indonesia uses the Post-Merger Notification System and voluntary notifications. The Pre-Merger Notification System is considered more effective in resolving the adverse impact of the merger implementation, which in this case is an abuse of the dominant position. From the perspective of Maqashid Syariah, the implementation of the Pre-merger Notification provides many benefits for business actors because it can provide certainty and certainty. The theory of maqashid Sharia aims to realize fame and avoid evil. Based on this, changes are needed regarding the merger notification system in Indonesia so that the policies made can provide benefits for business actors and provide a positive impact on consumers.